GERAK MANJA KUCING DALAM KARYA TAPERSTI - DINA YOLANDA, Drs. Erwin A, M.Sn., Dra. Zubaidah, M.Pd., (Serupa The Journal of Art Education, 2018)
An interesting cat spoiled motion makes the writer interested tovisualize it in the form of wall hangings. The purpose of the creation of this workis to realize the seven works of tapestry with the object of the pet cat spoiledmovement, while the method in the creation of this work is made through 3 stagesthrough tapestry, technique with soumak and giordes techniques.The result of the resulting cat motion spoiled motion is given theirrespective titles : Love, Warmth, Happiness, Loyalty 1, Togetherness, Loyalty 2and Spirit. It is hoped that the final work will be useful for art students, as anappreciation material and comparative work to create better tapestry in thefuture.Keywords: Cat spoiled motion, Tapestry, soumak and giordes.